Analysis of Relative Marketing Spending Efficiency Based on the Marketing-to-Revenue Ratio in Indonesian Retail Companies for the 2023-2025 Period - Lisa Polimpung; Fransisca Mulyono (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2026)
Purpose – This study aims to analyze the marketing-to-revenue ratio as an indicator of relative marketing expenditure efficiency in three retail companies in Indonesia and compare it across companies based on differences in business models. Design/methodology/approach – This research uses a comparative case study approach with secondary data from annual financial reports of PT Sumber Alfaria Trijaya Tbk (AMRT), PT Midi Utama Indonesia Tbk (MIDI), and PT Ramayana Lestari Sentosa Tbk (RALS) for the 2023-2025 period. The marketing-to-revenue ratio is calculated using the formula selling expense divided by net revenue multiplied by 100%. The analysis was conducted descriptively and comparatively by comparing ratios across companies and global benchmarks. Findings – The results show differences in the marketing-to-revenue ratio among the three companies. AMRT has an average ratio of 17.05% with an increasing trend and positive revenue growth. MIDI has an average ratio of 20.90% with a fluctuating trend and positive revenue growth. RALS has an average ratio of 4.15% with a decreasing trend accompanied by a decline in absolute revenue. Compared to the global retail industry benchmark (7.1%), AMRT and MIDI are far above it, while RALS is below it. However, being above or below the benchmark cannot be directly stated as efficient or inefficient without considering absolute revenue trends. Originality – This study contributes by showing that the interpretation of the marketing-to-revenue ratio cannot be separated from absolute revenue trends in a comparative case study of three retail companies with different business models in Indonesia.